Reproductive performance of captive-reared Indian white shrimp, Penaeus indicus, broodstocks over two generations - Anand, P. S. Shyne; Balasubramanian, C. P.; Aravind, R.; Biju, I. F.; Rajan, R. Vidhu; Vinay, T. N.; Panigrahi, A.; Sudheer, N. S.; Rajamanickam, S.; Kumar, Sujeet; Antony, Jose; Ambasankar, K.; et al. (Frontiers in Marine Science, 2023)
Closing the complex life cycle of closed thelycum shrimp in captivity is one of the fundamental challenges in breeding programs. In the present study, we investigated the sexual maturity, broodstock development, and spawning performance of two generations of captive-reared Indian white shrimp, Penaeus indicus, over 36 months originated from a single stock of wild brooders. The post larvae (GN-1) produced from wild P. indicus (G0) and P.L. (GN-2) produced from captive-reared (GN-1) broodstocks were nursery (1000 PL m-3) and grow-out (12 shrimp m-2) reared, and subsequently raised in broodstock ponds (1 shrimp m-2). The annual salinity and photoperiod in broodstock ponds varied between 20 to 36 ppt, and 11.2 -12.5 L and 11.5-12.8 D hours, respectively. The light intensity varied between 91 ± 6 lux at dusk to 75,358 ± 1719 lux at noon. The size at first impregnation or mating was 16.45 ± 1.7 g (132 DOC) and 17.62 ± 1.9 g (90 DOC), respectively, in GN-1 and GN-2 females. By 220 DOC, 25% of the GN-1 females initiated gonad development, whereas 55% of the GN-2 females recorded developing ovaries or were in stage II at 150 DOC. The broodstock attained an average final body weight of 38.85 ± 1.5 g (GN-1) and 42.65 ± 1.8 g (GN-2) by 360 DOC. The highest (p<0.01) eggs per gram body weight (5137 ± 303 eggs g-1) and hatchability, H (83 ± 0.7%), was recorded in wild broodstocks (G0) followed by GN-2 (1,715 ± 162 eggs g-1; H: 69 ± 2%) and GN-1 (1,476 ± 151 eggs g-1; H: 75 ± 1%). However, captive-reared broodstock had better survival (89-92%) than wild broodstocks (71 ± 0.8%). Further, indoor maturation trial (21 days) using ablated broodstocks (GN-1) revealed 79% of the impregnated broodstocks undergo molting, resulting in the loss of sperm pack and subsequent reduction in mating efficacy to 29%. The average sperm count and percentage of normal sperm also recorded (p<0.05) reduction during the maturation cycle. The data generated in the present investigation can form the baseline information for developing the breeding strategy for the genetic improvement of Indian white shrimp in India.